2023
DOI: 10.1021/acsami.3c03873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Missing-Linker Defects and Ion Exchange on Stability and Proton Conduction of a Sulfonated Layered Zr-MOF

Abstract: Intentionally introduced defects into solid materials create opportunities to control and tune their diverse physicochemical properties. Despite the growing interest in defect-engineered metal− organic frameworks (MOFs), there are still only a handful of studies on defective proton-conducting MOFs, including no reports on twodimensional ones. Ion-conducting materials are fundamentally of great importance to the development of energy storage and conversion devices, including fuel cells and batteries. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…391 Another recent example demonstrated by Matoga and coworkers investigated the effect of missing-linker defects present in a sulfonate-containing two-dimensional (2D) Zr-MOF, JUK-14, on the resulting proton conductivity. 392 The findings suggested that with missing-linker defects in the 2D Zr-MOF, higher proton conductivity values can be achieved at 60% and 75% RH compared to those achieved by the defect-free 2D MOF. The 2D Zr-MOFs reported here were also found to keep their structural integrity after the impedance measurements under a wide range of RH between 30% and 90%.…”
Section: Applicationsmentioning
confidence: 96%
“…391 Another recent example demonstrated by Matoga and coworkers investigated the effect of missing-linker defects present in a sulfonate-containing two-dimensional (2D) Zr-MOF, JUK-14, on the resulting proton conductivity. 392 The findings suggested that with missing-linker defects in the 2D Zr-MOF, higher proton conductivity values can be achieved at 60% and 75% RH compared to those achieved by the defect-free 2D MOF. The 2D Zr-MOFs reported here were also found to keep their structural integrity after the impedance measurements under a wide range of RH between 30% and 90%.…”
Section: Applicationsmentioning
confidence: 96%
“…The stability of the MOF materials directly affects their proton conductivity properties. Stabilized MOF structures can provide reliable pathways for proton conduction and thus support good proton conductivity properties. , From the comparison of PXRD patterns before and after electrochemical experiments, as shown in Figure , it can be observed that MOF- 1 and MOF- 2 exhibited well-matched patterns, indicating that the structure of MOF materials remained intact and active during the proton conduction process without significant damage or deactivation, thus preserving their conductivity activity.…”
Section: Resultsmentioning
confidence: 99%
“…As known from the literature reports, the presence of defects (i.e., “missing linkers”) in framework structures could significantly impact the MOF chemical, thermal, and mechanical stability. , Thus, it is plausible to suggest that the number of defects per metal node could be a variable that could explain the “gaps” found from the linker and metal consideration. The number of defects was evaluated for each of the prepared Th- and Zr-MOFs using the TGA-based reported procedure (Figure (top)). ,, As shown in Figure , an increase in the number of defects present in Th-MOFs decreases overall framework thermal stability, as evidenced by the variation of the MOF decomposition temperature, which is in line with the average number of defects per metal node.…”
Section: Resultsmentioning
confidence: 99%